Using Nanotechnology to Control Penicillium Digitatum - Atia, Emad Abd (American Journal of Botany and Bioengineering, 2025)
The application of nanomaterials to control several types of microbial species, such as agricultural pathogens and laboratory contamination, can lead to the preparation of new effective fungicides for the control of fungi. This research includes the preparation of silver nanoparticles (AgNPs) using green leaves of Allium cepa. One milliliter of AgNO3 solution was added to 99 milliliters of plant extract. After 45 minutes, the color of the solution became brown, indicating the formation of AgNPs. Several concentrations (0 ppm, 50 ppm, 100 ppm, 250 ppm, and 500 ppm) were prepared. One milliliter of each concentration was added to Petri plates before adding the PDA media. The antifungal action of silver nanoparticles produced through natural plant extracts was explored against Penicillium digitatum. The concentration of 500 ppm AgNPs showed the maximum antifungal action against Penicillium digitatum, with an inhibition rate of 68.46%, while the concentration of 250 ppm exhibited 53.85% inhibition. The lowest antimicrobial action was observed at 50 ppm, with an inhibition rate of 23.07%. Higher concentrations showed greater inhibition compared to lower concentrations, which can be attributed to the increased number of AgNPs at higher concentrations, allowing for broader coverage and better interaction with the fungal surface. The higher particle density enables more effective contact with and compaction of the fungal hyphae. Finally, it can be concluded that AgNPs are a viable substitute for other chemical formulations used in agriculture and the food industry as fungicides.